Effects of flurbiprofen axetil on postoperative renal function in patients undergoing percutaneous nephrolithotomy - Dong Wang; Zhiwei Wang; Dan Wang; Weixia Lei; Yue Lu; Yongxin Liao; Yingyuan Li; Pan Huang; Ning Shen (Medicine, 2026)
Background: This study aims to assess the impact of low-dose flurbiprofen axetil on the incidence of perioperative acute kidney injury (AKI) in patients undergoing percutaneous nephrolithotomy (PCNL). Methods: Between February and July 2025, 130 patients undergoing PCNL under general anesthesia at Huadu District People’s Hospital of Guangzhou were enrolled and randomly allocated to either the control group (Group C, n = 65) or the flurbiprofen group (Group FA, n = 65). Following surgery, patients in Group FA received 100 mg of flurbiprofen axetil intravenously, while Group C received 10 ml of normal saline. Serum creatinine, glomerular filtration rate (GFR), cystatin C, and neutrophil gelatinase-associated lipocalin (NGAL) levels were measured preoperatively and at 6, 24, and 48 hours postoperatively. Results: A total of 120 patients completed the study (Group C, n = 60; Group FA, n = 60). Baseline characteristics were comparable between the 2 groups ( P > .05). Five cases of AKI were observed in Group C, compared to one in Group FA, with no statistically significant difference ( P = .207). At 6 hours postoperatively, NGAL levels in Group C were significantly higher than in Group FA (216.35 ± 63.39 vs 184.84 ± 43.14, P = .002). No significant differences were found in serum creatinine, NGAL, or cystatin C levels at other time points. Conclusion: Postoperative administration of 100 mg flurbiprofen axetil may reduce NGAL levels at 6 hours after PCNL, indicating a potential protective effect on renal function.